Konstruksi Sistem Khilafah Hizbut Tahrir - Rofiq Al-Amin, Ainur (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This research traces and criticizes the construction of the Hizbut Tahrir caliphate. For this purpose, the researcher will process the data from Hizbut Tahrir's books by using qualitative approach. The results of this study show; first, the caliphate system promoted by Hizbut Tahrir which is claimed to be an inseparable part of Islamic teachings is wrong. Second, the structure of caliphate that constructed by Hizbut Tahrir is changing over time; beginning from Taqiyuddin an-Nabhani, Abd Qadim Zallum, and Ata Abu Rashta. Thus, Hizbut Tahrir’s claim that the structure of the caliphate has been perfect since the time of the Prophet is a false claim.